External growth strategies and organizational performance in emerging markets: The mediating role of inter-organizational trust - Alaaraj, S; Mohamed, ZA; Ummi Salwa Ahmad Bustamam (Emerald Group Publishing Ltd, 2024)
Indexed by WOS/Scopus